Profiles, antioxidative and ACE inhibitory activity of peptides released from fermented buttermilk before and after simulated gastrointestinal digestion. (March 2023) - Magouz, Osama; Mehanna, Nabil; Khalifa, Mohamed; Sakr, Hanaa; Gensberger-Reigl, Sabrina; Dalabasmaz, Sevim; Pischetsrieder, Monika
Abstract: Bioactive peptides, released from buttermilk by fermentation and/or gastrointestinal proteases, may have health promoting effects. Thus, a comprehensive analysis of the peptide fraction of fermented buttermilk, before and after different phases of simulated gastrointestinal digestion, was performed using ultra high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/MS). Results showed that digestion simulation substantially changed the peptide profile of fermented buttermilk. A total of 81, 120 and 46 peptides were identified in fermented buttermilk, its gastric and intestinal digests, respectively. These peptides released mostly from β-casein followed by αs1-casein, κ-casein and β-lactoglobulin. In addition, 14 peptides released from milk fat globule membrane proteins (lactadherin, butyrophilin and GlyCAM-1). Bioactivity, mainly angiotensin converting enzyme (ACE) inhibitory activity, has been reported before for only 54 of the detected peptides. Radical scavenging, ferric reducing and ACE inhibitory activities of fermented buttermilk peptides increased significantly after digestion, indicating promotion in fermented buttermilk-peptide bioactivity by gastrointestinal digestion. Graphical abstract: Unlabelled Image Highlights: Fermented buttermilk contains a unique peptide profile. Buttermilk peptides are released from both milk proteins and MFGM proteins. Fermented buttermilk peptides have antioxidant and ACE inhibitory activities. Both bioactivities increased significantly after gastrointestinal digestion. Peptides released from fermented buttermilk may have specific biofunctionalities.